Birds in the west coast of South Kalimantan, Indonesia - Maulana Khalid Riefani; Mochamad Arief Soendjoto (Society for Indonesian Biodiversity, 2021)
Abstract. Riefani MK, Soendjoto MA. 2021. Birds in the west coast of South Kalimantan, Indonesia. Biodiversitas 22: 278-287. There is no comprehensive data on birds in the west coast of South Kalimantan, yet the areas are pressured by human activities, especially the rapidly growing tourism. This study aimed to investigate the diversity of bird species that occurred in the west coast of South Kalimantan and to compare the similarities of bird communities across four villages used as the sampling sites, i.e. Sungai Rasau, Sungai Bakau, Tabanio, and Pagatan Besar. Transect method combined with concentration count method were used to record diurnal bird species and number of individuals in five replications from April to September 2020. The observation area was 100 m from the shoreline toward the sea and 400 m from the shoreline toward the inland along 2 km with observation time was 07.00-11.00 and 16.00-19.00. Shannon Wienner species diversity index (H'), a Dice community similarity index based on the presence or absence of species (ISD), and a community similarity index (modification) based on the number of individuals per species (ISM) were analyzed. In total, there are 101 bird species recorded belonging to 41 families with Sungai Bakau Village has the highest number of species (81 species), while Pagatan Besar Village is the lowest (62 species). Thirty-four species are categorized as waterbirds. Twenty-three species are categorized as migratory birds. In terms of diversity index from highest to lowest are Sungai Bakau (4.04), Sungai Rasau (3.95), Pagatan Besar (3.65), and Tabanio (3.48). The similarity of the ISD community ranges from 0.74-0.84, while the ISM ranges from 0.73-0.90. One case (Sungai Bakau - Tabanio) shows that community similarity based on the number of individuals per species is smaller than based on the presence or absence of species. Based on the protection status following Indonesian government regulation, most (84.16%) birds are categorized as unprotected, while based on the conservation status of IUCN, the majority (91.09%) are Least Concern. The results of this study can be used as baseline information for sustainable management of the area in various aspects, including future research (such as on pest and disease control), tourism (such as bird watching), and education (such as field guide).